The feminine in contemporary art: representation and contamination in the work of Helen Chadwick, Michèle Roberts and Helena Almeida - Coelho, Maria Luísa de Sousa (2012)
Tese de doutoramento em Ciências da Literatura (área de especialização em Literatura Comparada)